1961
DOI: 10.1113/expphysiol.1961.sp001519
|View full text |Cite
|
Sign up to set email alerts
|

The Respiratory and Cardiovascular Response to Immersion in Cold and Warm Water

Abstract: During their first few minutes of immersion in stirred water at 5 and 150 C. the pulmonary ventilation of twelve unclothed men was high, and their end-tidal PCO2 fell. The pCO2 then returned to or a little above its original level but did not greatly exceed it even in working experiments lasting 20 min. in water at 50 C. or 40 min. in water at 150 C. Although work reduced or reversed the initial fall in pCO2, these results therefore do not bear out predictions that the pCO2 would rise to dangerous levels durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

1961
1961
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 21 publications
1
48
0
2
Order By: Relevance
“…One of the possible explanations for this decrease was that hyperventilation preceded the measurements, resulting in lowered body stores of CO2. In the studies of Keatinge and Evans (11), minute volume of ventilation rose slightly after immersion in 350C water (up to the neck), but returned to normal after a couple of minutes. In our study, the measurement of CO2 output was done after at least 20 min of immersion.…”
Section: Resultsmentioning
confidence: 90%
“…One of the possible explanations for this decrease was that hyperventilation preceded the measurements, resulting in lowered body stores of CO2. In the studies of Keatinge and Evans (11), minute volume of ventilation rose slightly after immersion in 350C water (up to the neck), but returned to normal after a couple of minutes. In our study, the measurement of CO2 output was done after at least 20 min of immersion.…”
Section: Resultsmentioning
confidence: 90%
“…Burton (1941) reported that while heavily-clothed men generally had a poor metabolic response to cold, heavily clothed men used to life in a cold climate had a larger one, and Keatinge (1960) observed that exposure of men to air at 50 C for 160 min increased their metabolic response to a 30 minimmersion at 150 C later in the day. On the other hand the metabolic response of men immersed for 20 min in water at 150 C was reduced by repeated immersion at this temperature (Keatinge, 1959;Keatinge & Evans, 1961) and Scholander, Hammel, Hart et al (1958) observed lower metabolic rates and larger falls of skin and rectal temperatures during the night in aborigines than in Europeans sleeping out in Australia, where night temperatures were low but day temperatures were high. These various findings could be explained as adjustments made by the central nervous system, not necessarily at conscious level, in the light of experience obtained during acclimatization.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the early metabolic response to cold often observed, together with the decrease in metabolic rate at the end of the day always observed, after daily exposure to cold in the present experiments, can hardly be ascribed to anything other than central nervous adjustments of this kind. 216 W. B. KEATINGE ACCLIMATIZATION TO COLD This interpretation of changes in the metabolic response is in keeping with certain changes observed in other responses to cold; the heart rate and blood pressure response to immersion of a hand for 60 sec in ice-water, a painful cold stimulus, is reduced by repetition, probably through the central nervous system (Glaser & Whittow, 1957;Glaser, Hall & Whittow, 1959), and the respiratory and heart-rate, as well as the metabolic, responses of men to immersion for 20 min in water at 150 C are reduced by repeated immersion at this temperature (Keatinge & Evans, 1961).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human physiological response to acute cold exposure has been well documented, and substantial research has been conducted into adult thermal responses to initial and prolonged immersion in cold water (Golden & Tipton, 2002;Keatinge & Evans, 1961;Tipton, 1989). It is well recognized that the initial cold shock response seen in adults upon immersion includes uncontrollable respiratory gasping and increased cardiac workload that are particularly hazardous.…”
Section: Ijare Vol 9 No 2 2015mentioning
confidence: 99%